Performance testing of work shoes labeled as slip resistant - Jones, Taylor; Iraqi, Arian; Beschorner, Kurt (Applied ergonomics, 2018)
The variability in friction and slip propensity across slip resistant (SR) shoes is poorly understood. This study aimed to quantify the impact of shoe design features on the available coefficient of friction (ACOF) across shoes labeled as SR. Differences in ACOF and the slipping rate across SR shoes were also quantified. Twelve shoes were tested across five types of flooring and three contaminant conditions using a whole shoe mechanical slip tester. Geometric and hardness parameters were measured to determine the effect of heel outsole design on ACOF. The rate of slipping was evaluated for three of the shoes on vinyl tile with canola oil using human subjects. Differences in ACOF were significant across shoe outsole designs (p < .001). ACOF was correlated with geometrical and hardness parameters. Rate of slipping was lower for the highest ACOF shoe (p < .001). This information can be used to guide SR shoe selection and design. •Available coefficient of friction (ACOF) and rate of slipping were evaluated.•Performance was evaluated across different flooring and contaminant conditions.•Heel contact area and treaded heel width were positively correlated with ACOF.•Higher ACOF shoe reduced slip rate compared to lower ACOF shoes.•Outsole characteristics may be useful in slip resistant shoe selection and design.